Pengembangan Web Service Pada IoT Data Storage Dengan Pendekatan Semantik dan Penambahan Mekanisme Autentikasi - Tuti Wardani Hamid; Eko Sakti Pramukantoro; Andi Reza Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Internet of Things is one of technology that being popular every year. The ability of IoT to collecting information and data in the big scale and coming from many sources, make IoT needs middleware so that whole of data can be managed well. Data that has been collected will be saved on the data storage. To ease the process of shipping and process of saving data so that will be built API Web service that equipped with authentication and authorization's mechanism as security data. API Web service using Semantic Interoperability's concept so that data will more easy to understand. Functionality test shows that web service running as well as that function. With using web service on data storage in IoT's environment, so troubles in IoT data storage can be solved.